Efeitos fitotóxico ePhytotoxic and mito-depressive effects of Rosmarinus officinalis essential oil mito-depressivo do óleo essencial de Rosmarinus officinalis - Pawlowski, Ângela; Bastos, Kailany Panerai de; Kuzey, Camila de Abreu; Arruda, Bruna Lauriane de Oliveira de; Silva, Eliane Regina da (Acta Scientiarum. Biological Sciences, 2025)
Allelopathy is a phenomenon involving beneficial or adverse effects from one plant to another by releasing compounds called allelochemicals. Essential oils, which are volatile substances responsible for plant aromas, may play a role in this phenomenon. This study aimed to evaluate the phytotoxic and cytotoxic effects of rosemary (Rosmarinus officinalis) essential oil. Phytotoxic effects of the oil (1 µL, 5 µL, 10 µL, and 20 µL) were assessed on germination and initial growth of two target species: a crop (Lactuca sativa L., lettuce) and a weed (Eragrostis plana, capim-annoni-2). The evaluated variables were germination rate, speed of germination, root length, and shoot length. The cytotoxic effects of essential oil (0.5 µL, 1 µL, and 10 µL) were assessed on L. sativa root tips, evaluating its impact on mitotic and metaphasic indexes as well as the frequency of each mitotic phase. The essential oil was extremely harmful to L. sativa germination and initial growth. The volatiles also caused an inhibitory, dose-dependent effect in E. plana germination and strongly inhibited both root and shoot growth of the species at the highest amounts tested. Rosemary essential oil interfered with the cell division of L. sativa, resulting in decreased mitotic and metaphasic indexes. Analysis of the frequency of each mitosis phase indicates that volatiles inhibited root growth by delaying cell division. These findings suggest that rosemary essential oil could serve as a potential bioherbicide.